A multicriteria small modular reactor site selection model under long-term variations of climatic conditions – A case study for the province of Saskatchewan, Canada. (25th March 2021) - Zhang, Xiaoyue; Huang, Guohe; Zhou, Xiong; Liu, Lirong; Fan, Yurui
Abstract: Nuclear power has the potential to provide a clean solution to relieve environmental pressures caused by increasing fossil fuel consumption. As an emerging technology, small modular reactors (SMRs) are developed to tackle global needs for providing safe, clean, and economic energy. The identification of suitable sites for SMRs, which is a multifaceted process and includes multiple considerations, is a crucial step for their development. In this study, a climate-oriented SMR site recognition (CSSR) approach that reflects the long-term effects of climate change is developed to identify potential sites that are suitable for SMR placement. Specifically, annual mean temperature and annual maximum consecutive 10-day precipitation are considered under two future periods (i.e., 2040–2069 and 2070–2099) and two Representative Concentration Pathways (i.e., 4.5 and 8.5). In addition, economic and social factors, including transmission lines density, highway network density, distance to water bodies, population density and northern municipalities distribution are taken into account. To demonstrate the advantages of the proposed approach, a case study for Saskatchewan, Canada is conducted. It is expected that this study can provide a practical methodological framework for site identification of power plants under long-term variations of climatic conditions and can support Saskatchewan in initiating its nuclear power. Highlights: A climate-oriented SMR site recognition approach is developed. Multicriteria inference to support the site identification is carried out. High-resolution climate modelling is undertaken. A case study for Saskatchewan, Canada is conducted.